(untitled) (Wudil Journal of Science and Technology Education, 2025)
ICT stands for Information and Communication Technology. It is a generic term referring to a technology being used for collecting, storing, editing, and processingof information in various forms. Similarly, COVID-19 is a disease that has posed a devastating impact on public health in the world and Nigeria in particular. Above all, it has crippled theeconomic and socialactivities of the people as a result of the persistent lockdown imposed at various regular intervals when the disease was at its height in 2020. Against this background, therefore, this paper is a reflection on the role of ICT as it can be applied for the management of COVID-19 safety measures and other disease outbreaks in the country in the future. The paper examine the concept of information technology in the management of COVID-19 in Kano State. It also reviews some research work related to the role of management of information technology in keeping the people fully informed about their responsibilities in curtailing the spread of the virus. Methodologically, the paper uses a descriptive survey method and purposive sampling technique, which allows the selection of five local governments in Kano state, namely: Fagge, Dala, Nasarrawa, Tarauni, and Gwale local governments area of Kano State. Five fundamental questions were raised, in which 20 respondents were randomly selected from each of the local governments, and the questionswere administered to them. Data presentation and analysis: the result of the data from the field was analysed using percentages (%). The findings of the study reveal that ICT can be used to manage COVID-19 and any other disease outbreak in the future in Kano state. It also states that the power supply can limit the effective use of ICT in the state. The paper provides some recommendations for improvement in power supply and an increase in government funding in economic activities and the production of ICT materials.